Study of the evolution of antiemetic treatment through the application of Triadic Formal Concept Analysis - Ferreira, Lucas; Nobre, Cristiane; Zárate, Luis; Song, Mark (Anais do Symposium on Knowledge Discovery, Mining and Learning (KDMiLe), 2021)
Cancer treatment is always improving with new techniques and drugs, applied in a process with rigorous medical analysis. One way to analyze medical outcomes is to test a new drug in one group and placebos in another. In this article, we used a database with the results of a new drug for preventing chemotherapy-induced nausea and vomiting. After processing the database, we apply the Triadic Formal Concept approach to extract triadic rules, implications, and conditions that are used to identify correlations throughout the medical sessions. Our study shows that triadic analysis can help scientists perform clinical analyzes efficiently by looking at patient history data.